O padrão culto escrito em uso no Brasil em Gêneros Textuais do domínio jornalístico - Rosilene Alessandra Marques (2010)
This study aims to investigate the normative written standard being used in Brazil regarding the textual genres such as news, editorials, readers letter and journalistic articles. It is known that the context representation of the analyzed texts suggests the use of normative standard, besides being widely socially broad. To fulfill this purpose, the frequency of some linguistic facts which carry variation usage according to the differences concerning text supervision was raised in samples of the top pressed newspapers from each state of the country. The outcomeshows that the percentage of the linguistic usage that is coincident with the normative standard, whose reference is the traditional grammar, is significantly greater than the percentage of the non-usage of this normative standard. In addition to this, this study assures some preferences regarding the usage of the written normative standard in Brazil that have already been taken into account by other researchers (such as the use of the pronoun before the verb), and it also highlights some variations that may be taking place concerning the linguistic standard usage. Based on the outcomes from this study, it is believed that investigative texts should be used in the normative standard teaching/learning process, ist ed, texts that have effective social broadcast, as well as texts that follow the linguistic standard, inorder to disassociate the study of this linguistic norm of the literary tradition from contextless sentences and the strictly metalinguistic exercises.